Improving the nutritional value of grains by biological activation - Bazhay-Zhezherun, Svitlana; Romanovska, Tetiana; Antonіuk, Mariіa (My University, 2016)
Introduction. Cereal products are a source of carbohydrates, protein, macro and micronutrients, vitamins, enzymes, dietary fiber, phospholipids. Sprouting grains is one of the methods for biological activation. Materials and methods. Grains of wheat, triticale and naked oats have been studied. Protein was determined by Bradford method, the starch content – by poalrimetric method. Fat was determined by exhaustive extraction with chemically pure hexane. Vitamins B1, B2, B3, B6 were determined by the method of fluorometry. Vitamins PP and E were determined colorimetrically. Determination of vitamin C was performed by a titration method. Results and discussion. An important task in the process of preparing raw materials for health products is increasing their food and biological value. We proposed a regime of hydrothermal processing of grain at temperatures 12–16 °C. Under these conditions, activation of the enzyme complex, reduction of grain density and increase of its per unit volume; activation of the synthesis of vitamins and vitaminlike substance take place. In the process of biological activation of grain the bioavailability of proteins, carbohydrates, fat increases due to their partial hydrolysis. It has been studied, that the content of fibres,which is natural food sorbent, in biologically activated grains of wheat, naked oats and triticale is respectively 2,68, 2,34, 2,62%. It has been found that in the proposed processing of wheat, triticale and naked oats the quantity of vitamin C increased more than twice. The content of tocopherols increases tenfold, routine – 2,5–3 times. It was established that after hydrothermal treatment the total number of colony-forming units of mesophilic aerobic and facultative anaerobic microorganisms in native and dried corn samples is within the norms established by standards. Conclusions. The results are of practical importance, as they allow to recommend the use of biologically activated wheat, triticale, naked oats for the production of food of health, functional and health-care purposes.
Keywords: grain; зерно; wheat; пшениця; triticale; тритикале; oats; овес; кафедра технології оздоровчих продуктів